Integrated transcriptomic analysis reveals a CEBPB–DUSP1 axis driving tumor progression in colorectal cancer - Huarong Zhou; Lili Fang (PLoS ONE, 2025)
Colorectal cancer (CRC) is a prevalent and lethal malignancy, yet the transcriptional networks driving its progression remain incompletely defined. Here, we used integrated transcriptomic analyses of healthy and colorectal cancer samples from three datasets—TCGA-COAD, GSE100179 and GSE196006, and laboratory assays to uncover CCAAT/enhancer-binding protein beta (CEBPB) as a key driver of CRC. Elevated CEBPB expression in clinical samples correlated with shorter overall survival, suggesting its utility as a prognostic marker. We next identified DUSP1, a dual specificity phosphatase critical for MAPK regulation, as a direct transcriptional target of CEBPB. Motif enrichment and promoter scans revealed three high-affinity CEBPB-binding sites in the DUSP1 promoter. Luciferase reporter assays confirmed that CEBPB directly modulates DUSP1 transcription. Knockdown of CEBPB in HCT116 cells rescued DUSP1 expression and reduced pro-tumor pathways linked to hyperactive MAPK. The resulting phenotype showed decreased cell proliferation, enhanced apoptosis, and partial reversion of the malignant features typically associated with CRC. These findings underscore that CEBPB–DUSP1 dysregulation contributes to CRC aggressiveness, influencing both inflammatory and metabolic processes. Overall, this work highlights CEBPB as a potential biomarker for poor prognosis and points to the CEBPB–DUSP1 axis as a promising therapeutic target. Our findings also demonstrate the power of integrated transcriptomic approaches in elucidating intricate gene regulatory networks, offering a basis for new strategies to mitigate CRC progression.